Pengaruh Lama dan Suhu Penyimpanan Terhadap Mutu Minuman Teh Bunga Krisan Batik - Nasution, Indah S; Julianti, Elisa; Romauli, Nauas D M (Universitas Pattimura, 2025)
Batik chrysanthemum is one type of chrysanthemum whose use is limited to cut flowers. Chrysanthemum tea beverage processing is one form of product diversification that can increase the added value of chrysanthemum flowers. This study aims to determine the shelf life of chrysanthemum tea beverages packaged in glass bottles. This research design uses a factorial complete randomized design with two factors, namely storage temperature (room temperature and cold temperature (10 oC) as the first factor and storage time (0, 3, 6, 9, 12, and 15 days) as the second factor. Each treatment combination was made in 3 replicates; the results showed that the indication of temperature and storage duration gave a very significant effect (P < 0.01) on total phenolics, total flavonoids gave a significantly different effect (P < 0.05) on anthocyanin levels, and antioxidant activity. They gave a significantly different effect (P < 0.05) on the color index. The research results show that the ideal storage life of Chrysanthemum flower tea is at a cold temperature (10 °C). At this storage life, the chrysanthemum flower tea beverage has a high antioxidant activity and is acceptable for consumption.